2010
DOI: 10.1002/pd.2515
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall malformations in a 15‐year fetopathological study: accuracy of prenatal ultrasonography diagnosis

Abstract: Prenatal sonographic diagnosis is more accurate in omphaloceles than in gastroschisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…In 18% CHD was the only additional defect, in 26% other extracardiac defects were also present 11 . High prevalence of CHD in patients with omphalocele is also confirmed by the data from international medical literature, where CHD is reported in 15%-50% of the cases 5,6,7,15,16 . Boulton et al described abnormal heart axis with an excessive leftward rotation of the apex in more than a half of fetuses with omphalocele.…”
Section: Abnormalities Of Fetal Heart Function In Fetuses With Omphalsupporting
confidence: 56%
“…In 18% CHD was the only additional defect, in 26% other extracardiac defects were also present 11 . High prevalence of CHD in patients with omphalocele is also confirmed by the data from international medical literature, where CHD is reported in 15%-50% of the cases 5,6,7,15,16 . Boulton et al described abnormal heart axis with an excessive leftward rotation of the apex in more than a half of fetuses with omphalocele.…”
Section: Abnormalities Of Fetal Heart Function In Fetuses With Omphalsupporting
confidence: 56%
“…including maternal serum screening and fetal ultrasound [ 1 - 3 ]. Omphalocele is caused by failure of the four mesodermal-derived folds (left, right, cranial and caudal) to fuse at approximately 3 to 4 weeks of embryonic development (abdominal wall formation failure theory).…”
Section: Introductionmentioning
confidence: 99%
“…However this only amounted to 54 studies in total as some artices described different tests from the same study. Of the 134 indirect evidence papers or abstracts, 133 were synthesised41–174 as well as a single trial record 175. None of the seven included trials identified from trial registries reported interim or final results and only four remain active 176–179.…”
Section: Resultsmentioning
confidence: 99%
“…For both risk of bias and applicability to the review question, the majority (n=129) had some concerns,41 42 44–67 69–87 89–149 151–170 172–174 and five had a high level of concern43 68 88 150 171 (figure 3).…”
Section: Resultsmentioning
confidence: 99%